2016
DOI: 10.1186/s13071-016-1605-3
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Neglected Tropical Diseases diagnostics: the sensitivity of skin snips for Onchocerca volvulus in near elimination and surveillance settings

Abstract: BackgroundThe African Programme for Onchocerciasis Control has proposed provisional thresholds for the prevalence of microfilariae in humans and of L3 larvae in blackflies, below which mass drug administration (MDA) with ivermectin can be stopped and surveillance started. Skin snips are currently the gold standard test for detecting patent Onchocerca volvulus infection, and the World Health Organization recommends their use to monitor progress of treatment programmes (but not to verify elimination). However, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…Another is for PCR confirmation of a suspected patent infection in a person who is Ov16 positive, as noted in the WHO Guidelines. Regardless, given these core mitigating factors noted above, we believe that Bottomley et al [1] erred in calling for the use of skin-snipping as a method to determine whether to stop MDA and as a post-MDA surveillance procedure. The 2016 WHO Guidelines for the verification of elimination of onchocerciasis state emphatically that the use of skin snips is to be avoided as a means to determine whether or not to stop MDA, and to monitor post-MDA status as a lead up to verification of interruption of transmission.…”
Section: Letter To the Editormentioning
confidence: 99%
See 4 more Smart Citations
“…Another is for PCR confirmation of a suspected patent infection in a person who is Ov16 positive, as noted in the WHO Guidelines. Regardless, given these core mitigating factors noted above, we believe that Bottomley et al [1] erred in calling for the use of skin-snipping as a method to determine whether to stop MDA and as a post-MDA surveillance procedure. The 2016 WHO Guidelines for the verification of elimination of onchocerciasis state emphatically that the use of skin snips is to be avoided as a means to determine whether or not to stop MDA, and to monitor post-MDA status as a lead up to verification of interruption of transmission.…”
Section: Letter To the Editormentioning
confidence: 99%
“…We read with interest the recent article by Bottomley et al [1] and were surprised that the authors concluded that skin snips have utilitarian value in evaluating the efficacy of onchocerciasis elimination programs three years after final mass drug administration (MDA). We strongly disagree that skin snips would have any practical utility in this or any other operational scenario in assessing whether to stop MDA or in post MDA transmission elimination monitoring.…”
Section: Letter To the Editormentioning
confidence: 99%
See 3 more Smart Citations